Changing our textual minds : towards a digital order of knowledge - Weel, Adriaan van der. (Manchester : Manchester Univ. Press, 2011)
'Text has always been the chief vehicle for the inscription and dissemination of knowledge and culture. As more and more of our textual communication moves into the digital realm we have reached a crucial moment in the history of textual transmission. In many respects digital text looks deceptively like print. But beneath the surface of the screen, digital textuality obeys very different rules than printed text. The digital textual universe offers a wealth of new and exciting possibilities--but it also sets new rules for the writer's and reader's engagement with text. Changing our textual mind analyses the continuities and discontinuities in textual transmission as we move from a print paradigm into an increasingly digital world. It conceptualises the epochal transition from analogue to digital both in factual terms and in terms of its social significance. Centuries of reading and writing practice have made us Homo typographicus. Our entire way of disseminating knowledge and culture is firmly based on print culture. The need to come to grips with the shift to digital textuality in the early twenty-first century will literally change our minds.'--Publisher's website.
Introduction: from the'order of the book' to a digital order? -- A textual universe -- Concepts in textual mediality -- The order of the book -- A brief history of text and the computer -- Salient features of digital textuality -- Coda.
Includes bibliographical references and index.
Keywords: Electronic information resources -- Social aspects; Digital media -- Social aspects